Preoperative diagnosis of portal vein invasion in pancreatic head cancer: appropriate indications for concomitant portal vein resection. (5th September 2016) - Teramura, Koichi; Noji, Takehiro; Nakamura, Toru; Asano, Toshimichi; Tanaka, Kimitaka; Nakanishi, Yoshitsugu; Tsuchikawa, Takahiro; Okamura, Keisuke; Shichinohe, Toshiaki; Hirano, Satoshi
Abstract: Background: The surgical indications for patients with pancreatic head cancer (PHC) with clinical portal vein (PV) invasion (cPV) remain controversial. The present study aimed to determine the ability of computed tomography (CT) to diagnose pathological PV involvement (pPV) in PHC. Methods: We evaluated the morphological features (length and circumference) and two sets of diagnostic criteria for cPV determined from preoperative CT findings of 112 consecutive patients who underwent pancreatoduodenectomy for PHC. This study is listed in the UMIN Clinical Trials Registry (UMIN‐CTR; No: UMIN000016827). Results: Five patients were excluded because enhanced CT data were missing. Morphological features have low diagnostic ability for pPV. We diagnosed 67 patients with cPV based on our diagnostic criteria and those of Klauss, and 42 of them had pPV. The negative predictive values of these diagnostic criteria for pPV were satisfactory (>95%) and the positive predictive value was relatively low (61.2%). Postoperative survival could be predicted based on the cPV type. Conclusion: An accurate diagnosis of pPV based on morphological features determined by preoperative CT is difficult. However, preoperative CT appears useful for selecting patients with PHC who could be candidates for pancreaticoduodenectomy with or without PV resection. Abstract : Highlight Teramura and colleagues set out to determine clinical portal vein invasion (cPV) on the basis of preoperative computed tomography findings in patients with pancreatic head cancer. The negative predictive values were satisfactory and the positive predictive values were relatively low. Postoperative survival could be predicted based on the cPV type.